Antibody Response of Animals to Mycoplasma pneumoniae Measured by Latex Agglutination - Kende, Meir (1969)
The standardization, application, and usefulness of latex agglutination for Mycoplasma pneumoniae antibody titration were investigated and compared with tetrazolium reduction inhibition and complement fixation. The sera of guinea pigs and monkeys reacted in a specific fashion, whereas rabbit serum required pretreatment to eliminate its nonspecific agglutinin. Human serum given such pretreatment still contained a nonspecific agglutinin. The latex agglutination procedure compared favorably with complement fixation and metabolic inhibition tests for evaluating vaccine antigenicity.